Diabetes Education in Family: Risk Factors and Barriers to Diabetes Care in Mexican Children and Adolescents - Leal, María del Carmen Enríquez; Tamayo, María del Socorro Saucedo; Ochoa, María Guadalupe Vidal; Vásquez, Martha Nydia Ballesteros; Pacheco, Rosa María Cabrera; Figueroa, Cecilia Adriana Montaño; Vélez, María Isabel Ortega (International Journal of Child Health and Nutrition, 2011)
Objective: To determine barriers related to metabolic control and diabetes care in Mexican children and their families. Design: This was a cross-sectional study designed in two stages. First stage was an assessment of risk factors for inadequate metabolic control (HbA1c higher than ADA guidelines by age group) of diabetic children using a logistic regression model. The data sources were 91 clinical files provided by public health institutions at northwest Mexico. Second stage included the design, implementation and evaluation of an educational program (EP) based on the Medical Nutrition Therapy (MNT) and the Social Cognitive Theory (SCT), accounting for critical risk factors identified previously. Twenty five children (2 to 14 years old) with type 1 diabetes and their parents agreed to participate in the EP, which promoted healthy behavioral changes regarding diet, physical activity and medical treatment over a 4-month period. Results: Metabolic control was related to the joint effects of families low socioeconomic level and mother’s low education attainment (OR= 8.5, CI95%: 1.73, 42.16), as well as following a conventional treatment (OR= 5.0, CI95%: 1.09, 22.82). After program implementation participants’ mean glycated hemoglobin (HbA1c) decreased (9.1%±1.8% to 8.3%±2%; P=0.06). Qualitative content analysis of post-intervention interviews showed that low income, clinical inertia, and lack of social support were barriers to metabolic control of diabetes. Conclusion and Implications: Socioeconomic, educational, and healthcare factors are related to metabolic control in Mexican children with diabetes, although educational programs based on SCT can help increase self-efficacy in patients through modeling and reinforcing activities.